Anomia Perception, Trust and Well Being: a view from the Social Psychology - Muratori, Marcela (2013)
An empirical research was carried out with the aim of exploring in levels of anomy, social well-being and institutional trust and their relationship. Is a descriptive correlation study with a non experimental design based on a convenience sample composed by 585 participants (34.7% males and 65.3% females, age: M = 28.50; SD = 11.02) from Buenos Aires and other Argentinian cities. Results show a general positive perception of social well being -with a lack in others confidence-, low levels of institutional trust and high punctuations inanomic frustration. Convergent validity was corroborated and group differences showed up.